Determinants of philanthropy donation among individual Muslim: a case study in Kuala Pilah Negeri Sembilan / Fara Syuhdila Khalid - Khalid, Fara Syuhdila (Faculty of Business and Management, 2015)
Philanthropy is a society instruments for sensitive and chronic challenges that appear in the world around us. It has been practiced in a long time ago and honoured by every religious tradition. Most of the research in this discipline has been conducted by the American and European context, while, research in the context of Asian countries is limited. Therefore, the purpose of this study is to identify the determinants of philanthropic donation in Kuala Pilah, Negeri Sembilan area. There are four (4) determinants of philanthropic donation in this research which are demographic factor, attitude and perception, transparency and accountability and well– being. This study follows intercept method using survey method. A set of questionnaire were distribute around Kuala Pilah area. Frequency analysis, descriptive analysis, reliability analysis and correlation analysis have been chosen as the moethod to find the result. The finding indicated that well – being is the most factor that determining the philanthopic donation in Kuala Pilah area as compared to attitude and perception, transparency and accountability and demographic factor. As for future researcher, it recommended that this study can be conducted at different state in Malaysia to know more about the determinants of philanthropic donation.